A POSITIVE SOCIALIZATION MODEL FOR CHILDREN WITH AUTISM SPECTRUM DISORDERS: COMPREHENSIVE AND INTERDISCIPLINARY APPROACHES. Part 2. Russian experience in social-psychological support of children with asd and their families - Albina A. Nesterova (Obrazovanie i Nauka, 2016)
Abstract. The second part of the article aims to analyze domestic experience in support of children with autism; to show the complex model of support of positive socialization of children with ASD and severe defects; to justify the necessity of creating a scientifically validated complex model of support of children with ASD. Methods. The methods involve theoretical analysis and summarization of scientific and methodical publications on the issue of socialization of children with ASD; modeling method. Results. Scientific approaches to socialization and social integration of children with ASD are analyzed, summarized and systematized. The most efficient empirically validated methods and techniques that may be included in the process of social-psychological support of children with ASD and their families are indentified. Regional experience of the Russian Federation in solving the issue of socialization of children with ASD and their families is uncovered, the most effective programs and developments of domestic specialists are highlighted. The model of support of the positive socialization of children with ASD is developed and validated. Scientific novelty. The proposed model is developed on the basis of the principles of multidisciplinarity and interdisciplinarity in the process of interaction between specialists of support, aimed at solving socialization problems of children with ASD and their families. The model incorporates such basic conditions of positive socialization of a child with ASD as: a state of mental health of a child; creation of conditions for successful process of socialization of a child, in particular, for the formation of basic social skills; provision of close interaction of children, psychologists, teachers, parents, social partners; monitoring of dynamics of total indicators of social competence and development of children. Practical significance. The model is supposed to be the basis while creating support for children with ASD at public schools and correctional schools, organizations with inclusive practice, social-rehabilitation centers for minors, in the system of vocational development for teachers, doctors, social rehabilitologists, psychologists, specialists of correctional pedagogy.